2006
DOI: 10.1080/01411920500401997
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grammar teaching on writing development

Abstract: This article reports on the results of two international systematic research reviews which focus on different aspects of teaching grammar to improve the quality and accuracy of 5–16-year-olds' writing in English. The results show that there is little evidence to indicate that the teaching of formal grammar is effective; and that teaching sentence-combining has a more positive effect. In both cases, however, despite over a hundred years of research and debate on the topic, there is insufficient quality of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 8 publications
2
68
2
10
Order By: Relevance
“…A growing body of research from conventional and special education classrooms demonstrates that the specific teaching of the component skills of writing improves the quality of children's written compositions. [51][52][53][54] With respect to teaching mathematics to young children, there are many recommendations that Montessori teachers would recognise in their own classrooms, such as teaching geometry, number and operations using a developmental progression, and using progress monitoring to ensure that mathematics instruction builds on what each child knows. 55 Some of the recommended activities, such as 'help children to recognise, name, and compare shapes, and then teach them to combine and separate shapes' 55 map exactly on to Montessori's sensorial materials such as the geometric cabinet and the constructive triangles.…”
Section: Evaluations Of Key Elements Of Montessori Education That Arementioning
confidence: 99%
“…A growing body of research from conventional and special education classrooms demonstrates that the specific teaching of the component skills of writing improves the quality of children's written compositions. [51][52][53][54] With respect to teaching mathematics to young children, there are many recommendations that Montessori teachers would recognise in their own classrooms, such as teaching geometry, number and operations using a developmental progression, and using progress monitoring to ensure that mathematics instruction builds on what each child knows. 55 Some of the recommended activities, such as 'help children to recognise, name, and compare shapes, and then teach them to combine and separate shapes' 55 map exactly on to Montessori's sensorial materials such as the geometric cabinet and the constructive triangles.…”
Section: Evaluations Of Key Elements Of Montessori Education That Arementioning
confidence: 99%
“…Cette modalité n'a pas été traitée dans les études recensées, probablement à cause de la difficulté à l'opérationnaliser. De toute façon, il semble qu'un consensus soit apparu depuis, en enseignement des langues secondes, quant à la pertinence d'enseigner explicitement l'écriture (Andrews, R., Torgerson, C., Beverton, S., Freeman, A., Locke, T., Low, G., Robinson, A. et Zhu, D. 2006 ;Ellis, 2006), bien que l'on reconnaisse la valeur ajoutée des apprentissages implicites (Perruchet et Pacton, 2004). On pourrait, par contre, considérer cette modalité pour l'enseignement des structures de textes, par exemple, au contact de ceux d'autres auteurs, en visant un transfert des connaissances par modélisation.…”
Section: Tableau 1 Les Méthodes Pédagogiques Inductives Et Déductivesunclassified
“…Two significant large-scale meta-analyses (Andrews et al, 2006;Hillocks, 1986) found no evidence of a relationship. It should be noted that these studies concern the teaching of grammar separated from the teaching of writing.…”
Section: Grammar Teachingmentioning
confidence: 99%